I'm not going to have a conversation with you: Linguistic refusals of 1st Amendment YouTube auditors during police interactions. Issue 2 (3rd July 2022) - Perez, James
ABSTRACT: This article examines the opening linguistic interactions between police officers and First Amendment auditors. First Amendment auditing is a relatively new movement in which individuals visit government-funded entities, such as a police department, and then videotape the encounter with the public officials. The vast majority of these auditors are individuals working independently, or citizen journalists. Examples of officers approaching auditors are examined to argue both parties deploy structured responses during these encounters. Police officers initiate conversations with auditors by deploying three various language structures: inquisitive linguistic strategies (asking questions), directive linguistic strategies, (giving commands), or a greeting. Despite the variety of linguistic structures, however, the argument is all three openings spoken by the police officers function as commands. The study also examines how First Amendment auditors linguistically respond to the commands of officers with refusals.